2012
DOI: 10.1136/heartjnl-2011-301076
|View full text |Cite
|
Sign up to set email alerts
|

Prior antiplatelet or anticoagulant therapy and mortality in stroke

Abstract: Objective To examine the influence of previous antiplatelet or anticoagulant therapy on subsequent stroke mortality at different time points up to 1 year post stroke. Design Data were examined from a hospital register collected over 5 years (2004e2008). Setting A single large university hospital. Participants Every adult (18+ years) admitted with an acute stroke. Main outcome measures Mortality risks at 7, 30, 60, 90 and 365 days were assessed using logistic regression following ischaemic and haemorrhagic stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 31 publications
(29 reference statements)
2
23
0
Order By: Relevance
“…It has been hypothesized that aspirin, if administered before acute ischemic stroke onset, may be of value as an agent that may reduce initial stroke severity and improve overall clinical outcome 4, 5, 6, 7, 8, 9, 10. Some studies have shown an association between prestroke antiplatelet use and lesser stroke severity,4, 5, 6 whereas others have not 7, 8, 9.…”
mentioning
confidence: 99%
“…It has been hypothesized that aspirin, if administered before acute ischemic stroke onset, may be of value as an agent that may reduce initial stroke severity and improve overall clinical outcome 4, 5, 6, 7, 8, 9, 10. Some studies have shown an association between prestroke antiplatelet use and lesser stroke severity,4, 5, 6 whereas others have not 7, 8, 9.…”
mentioning
confidence: 99%
“…2 Better understanding of such determinants is important because these stroke subtypes have different pathophysiologies, different risk profiles, and different survival trajectories. 12 These cannot be tested in randomized trial setting, and such real-world events needed to be observed and reported through registry data. In this study, we examined the determinants and outcomes of ischemic and hemorrhagic stroke associated with PCI for ACS compared with those who underwent elective PCI using the British Cardiovascular Intervention Society registry in England and Wales, including over half a million participants.…”
mentioning
confidence: 99%
“…In the aforementioned Canadian study, in-hospital mortality rates also did not differ between patients who were on clopidogrel prior to ischemic stroke and those who were not on antiplatelet agents [13] . In a more recent small study, mortality at 7 and 30 days after stroke did not differ between patients who were receiving clopidogrel prior to ischemic stroke (n = 63) and those who were not [20] . However, all types of ischemic stroke were included in the former report and stroke severity at admission was not evaluated and not adjusted for in the analysis of mortality risk [20] .…”
Section: Discussionmentioning
confidence: 99%
“…However, other reports did not confirm these beneficial effects of aspirin [15][16][17][18][19] . On the other hand, very few studies assessed the effects of prior treatment with clopidogrel on acute non-cardioembolic ischemic stroke severity and outcome and yielded conflicting results [13,17,20] . If treatment with clopidogrel before stroke attenuates stroke severity and improves outcome, this would further support its use as a first-line agent in patients with non-cardioembolic ischemic stroke, who are at high risk for recurrent stroke.…”
Section: Introductionmentioning
confidence: 99%